Designing Visual Identity for Wedding Decoration to Enhance Brand Awareness - Muhammad Ammar Shiddiq; Ambar Aditya Putra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2026)
Wedding Decoration Nana Beckham is a wedding decoration business based in Way Kanan, Lampung, which has been running for over 15 years but still lacks a strong and consistent visual identity. The absence of a visual identity makes it difficult for the business to differentiate itself from competitors and build brand awareness. This study aims to design a comprehensive visual identity system that strengthens the business’s image and expands its market reach. The design process involves observation, interviews, and SWOT analysis to understand the business's needs and characteristics. The final outcome includes key visual elements such as logo, typography, color palette, and their application across various promotional media, along with the development of a Graphic Standard Manual (GSM). The new visual identity is intended to represent the brand's aesthetic values, local culture, and professionalism, thereby enhancing its competitive advantage and increasing brand awareness.